The learning factory through the sustainability lens - Milisavljevic-Syed, Jelena; Afy-Shararah, Mohamed; Sahin, Orhan; Salonitis, Konstantinos (SSRN, 2023)
Manufacturing organizations are facing increasing global pressures to be more digitalized, sustainable, and lean. Whereas the manufacturing industry is facing a shortage of demanding competencies of Industry 4.0., because the talent pool is either dry or the knowledge related to such skills is still not clearly formulated. Learning factories, through their triangular depth of education, research, and training, have been seen by many researchers in recent years as suitable environments to address these gaps in knowledge and skills. Although it is very useful for academia and industry alike, not much has been found on how to develop a learning factory. In this paper, the authors propose a new morphology and shed light on the sustainability that should be addressed when designing or reconfiguring learning factories. They provide existing limitations and future challenges and questions as research opportunities that must be addressed to further advance this learning environment.
© The Authors
Keywords: learning factory; morphology; sustainability; competencies development